Average treatment effect of robotic versus laparoscopic rectal surgery for rectal cancer. Issue 2 (28th December 2020) - Solaini, Leonardo; Perna, Federico; Cavaliere, Davide; Vaccaro, Carla; Avanzolini, Andrea; Cucchetti, Alessandro; Coratti, Andrea; Ercolani, Giorgio
Abstract: BACKGROUND: The aim of this study is to estimate what would have happened if all patients treated with laparoscopy for rectal cancer had instead been treated with the robotic technique. METHODS: To estimate the average treatment effect (ATE) of the robotic technique over the laparoscopic approach, data from patients treated at two centres between 2007 and 2018 were used to obtain counterfactual outcomes using an inverse probability weighting (IPW) adjustment. RESULTS: This study enrolled 261 patients, of which 177 and 84 patients had undergone robotic surgery and standard laparoscopy, respectively. After IPW adjustment, the difference between the groups was similar in the pseudo‐population. The average conversion rate would fall by an estimated 6.1% if all procedures had been robotic ( p  = 0.045). All other post‐operative variables showed no differences regardless of the approach. CONCLUSION: ATE estimation suggests that robotic rectal cancer surgery could be associated with a lower conversion rate. The approach did not affect the post‐operative morbidity rates or the operative time.